Pemodelan dan Rekomendasi Perbaikan Proses Bisnis Divisi Akademik Menggunakan Metode Business Process Improvement (BPI) (Studi Pada: Bina Avia Persada Malang) - Dio Rahmat Putra; Aditya Rachmadi; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The academic division is the main service in training supporting at Bina Avia Persada Malang. Bina Avia Persada Malang is an educational and training institution that prepares human resources who are ready to work for flight attendants, ground handling and ticket reservation. In running a business process, there are often obstacles that cause business process services to be not optimal. So it is necessary to do analysis and modeling business process in order to find recommendations for business processes improvement that can improve business process services to be more effective and efficient. In the analysis and evaluation of business processes carried out using the following methods: Failure Mode and Effect Analysis (FMEA) to identify and prevent problems. This method is used to find problems that occured, potential problems and problem effects by using 3 parameters, that is severity level, occurrence level and detection level. Meanwhile, the method used in this business process improvement is BPI approach. This method serves to facilitate researchers in identifying, modeling and making improvements to academic service objects. So that the use of this method can determine the improvement of business processes by trimming unnecessary services and maximizing the use of assets of Bina Avia Persada Malang.